CERITA BERBINGKAI DALAM LE SERVICE DES MANUSCRITS KARYA ANTOINE LAURAIN - Yolanda Latjuba, Ade; Salsabila Fitriana, Ismail; Irma Nurul Husnal, Chotimah (Universitas Hasanuddin, 2024)
This research aims to present the narration's structure, identify the narrator's type and positions, and identify the type of focalization. The method used in this research is qualitative, with an objective approach focusing on intrinsic elements of the novel. Based on the analysis of the data, it was found that the novel Le service des manuscrits employs the framed narrative technique, with inserted text that serves to explain and complement the primary text. The narrator in this novel is of the heterodiegetic type, situated at the metadiegetic level. The type of focalization in this novel is variable focalization. The framed storytelling technique in Le service des manuscripts provides a distinctive yet complex reading experience, as the layered structure of the story universe is narrated and focalized through several types of narrators and characters involved in the story.